Decreased serum ghrelin following Helicobacter pylori eradication - Mantero, P. (2023)
Objective: Ghrelin is an appetite-modulating peptide mainly produced in the stomach, with levels reported to be lower in Helicobacter pylori-positive subjects. This pre-post study aimed to evaluate the effect of H. pylori eradication on circulating total ghrelin, gastric histopathology, appetite, and nutritional status of dyspeptic adults.Patients and Methods: Weight, height, appetite and nutrient intake were determined using validated tools. Gastric biopsies were obtained for histopathology and H. pylori diagnosis. Fasting serum ghrelin was measured by ELISA. H. pylori-positive subjects received eradication therapy and returned ≥12 weeks later for re-evaluation.Results: Of 117 screened individuals, 47 who were H. pylori-positive were included, and the organism was eradicated in 28 (59.6%). Pathologic findings decreased significantly after treatment in subjects with eradication (p<0.0001) but did not in those without. Appetite and nutrient intake did not differ significantly after therapy in either group; however, body weight increased in both (p=0.02 and p=0.03). Fasting serum ghrelin significantly decreased in subjects with eradication [345.0 pg/mL (IQR 373.0-517.8) before, 298.5 pg/mL (IQR 251.0-383.5) after; p=0.0007] but remained unchanged in those without. Conclusions: The decrease in fasting ghrelin after H. pylori eradication indicates its involvement in the regulation of this hormone, which may be mediated by the inflammatory responses in tissues to the organism.